Development Of Photo-Curable PMMA-Based Liquid Resin: Dispersibility Study Of Go And Ago In PMMA-Based Liquid Resin And Mechanical Analysis Of Composites - Sim, Yeap Feong (Universiti Sains Malaysia, 2022)
Amine-functionalization of graphene oxide (GO) was performed using ethylenediamine (EDA) under heating to produce aminated graphene oxide (AGO). The successfulness of AGO produced was confirmed by using FTIR analysis. The photo-curable PMMA liquid resin was successfully produced by simply mixing the PMMA powder into MMA liquid with some heating. Then, the solution was added with photo-initiator, Irgacure 819 at room temperature. After that, 0.1wt%, 0.2wt% and 0.5wt% of GO and AGO were dispersed into the most dilute PMMA liquid resin which then used to study the dispersibility of GO and AGO inside the PMMA liquid resin. The result showed that for 0.2 wt% of GO and AGO, the zeta potential value of PMMA resin was the highest, indicating the PMMA colloids were highly charged, and the stability was caused by the electrostatic repulsion between the particles. Then, 0.2 wt% of GO and AGO was chosen for fabrication of PMMA composites under different UV light source. The polymerization was done by three different method which were by Creality Halot-one 3D resin printer, UV irradiation chamber and Cure Spot. However, only Cure Spot method successfully polymerized the PMMA liquid resin. The degree of conversion was used to evaluate the degree of curing of PMMA at different loading of Irgacure 819. It can be concluded that the higher amount of photo-initiator gives higher degree of conversion at fix curing time and irradiation source. After that, tensile test was done and the result was compared. The result showed that tensile strength of PMMA filled with GO and AGO higher than unfilled PMMA, tensile strength of GO higher than AGO and tensile strength of 0.5 wt% Irgacure 819 higher than 0.2 wt% Irgacure 819 at same amount of PMMA and MMA.